The Evaluation of Effect of 60-Days Sodium Benzoate Administration on Phase Composition of The Tibiaâ€™ Regenerate by Two-Way Anova - N. Krikun, Evgeniy; V. Luzin, Vladyslav; N. Fastova, Olga; N. Morozov, Vitaliy; N. Morozova, Elena (International Journal of Engineering and Technology, 2018)
Currently, sodium benzoate is widely used in the food industry, cosmetology and medicine. The literature provides information about the effect of its introduction on the growth and shaping of bones, the parameters of the crystal lattice of the regenerate formed therein. However, information about the effect of this food additive on the phase composition of the bone regenerate being formed and the degree of this influence is practically absent, which was the purpose of the study. The experiment was conducted on 210 white male rats, divided into 6 groups: 1st - control animals, 2nd and 3rd - rats, daily receiving intragastrically 1 ml of sodium benzoate 500 and 1000 mg/kg/day, respectively for 60 days. The 4th group - rats being inflicted a defect in both tibial bones, and the 5th and 6th - rats being inflicted a defect after the end of the 60-day injection of sodium benzoate. The timing of the experiment after the introduction of sodium benzoate was 3, 10, 15, 24 and 45 days. The area of the forming regenerate of tibial bones was investigated by X-ray diffraction analysis: the percentage content in the mineral of the regenerate of whitlockite, hydroxylapatite and calcite was calculated by the method of internal control. The impact of the introduction of sodium benzoate and the application of the defect on the above indicators was evaluated by two-factor analysis of variance. The results of the study showed that 60-day administration of sodium benzoate leads to an increase in the amorphism of the biomineral of the forming regenerate of tibial bones, the severity and recovery rate of which depends on its administered dose. Thus, the group being inflicted the defect of the tibial bones after the completion of the 60-day administration of sodium benzoate at a dose of 500 mg/kg/day had greater calcite content on day 10 to 45 by 17.88%, 12.88% and 6.63%, and whitlockite - on day 3, 24 and 45 by 14.30%, 4.52% and 6.20%, and hydroxylapatite - less on day 15 to 45 by 3.11%, 3.31% and 2.14%, compared with the defect-inflicted group without the introduction of sodium benzoate. An increase in the administered dose of sodium benzoate up to 1000 mg/kg/day led to aggravation of the identified deviations: the whitlockite content on day 3, 24, and 45 was higher by 16.15%, 6.21% and 9.54%, and the hydroxylapatite content on day 15 to 45 was lower by 3.98%, 4.16% and 3.34%. The conducted two-factor analysis of variance showed that the introduction of sodium benzoate had a significant effect on the change in the content of calcite, whitlockite and hydroxylapatite in the regenerate, the strength and duration of which depends on its administered dose. The maximum power of influence was registered for the increased content of calcite and the decreased content of hydroxylapatite in the mineral of the regenerate on day 45 of the experiment, and for the increased content of whitlockite - on day 3. When a defect was inflicted, the power of influence was maximal for the increased content of calcite and decreased content of hydroxylapatite on day 10, and the increased content of whitlockite - on day 15. In this case, a reverse dose-dependent effect was observed in all periods of the experiment.Â Â